Kepentingan Ekonomi Indonesia melalui Perjanjian Indonesia – Uni Arab Emirates Comprehensive Economic Partnership Agreement (IUAE-CEPA) - Oxanna Jean Wa’Uina; Novriest Umbu W. Nau; Roberto Octavianus Cornelis Seba (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Indonesia and the United Arab Emirates have maintained a harmonious bilateral relationship since the establishment of diplomatic relations in 1976. In the economic sector, dynamics relationship between the two countries reached a peak with the agreement of the comprehensive IUAE-CEPA. Indonesia subsequently leveraged this cooperation as an implementation of economic diplomacy to fulfill its national economic agenda. Therefore, this study aims to understand Indonesia's economic interests through the Indonesia-United Arab Emirates Comprehensive Economic Partnership Agreement (IUAE-CEPA). The author uses the theory of liberalism and the concept of national interest as analytical tools. The type of research conducted is qualitative research using descriptive methods. The author also collects data and information through literature studies, then summarizes and analyzes this data using data reduction techniques to draw conclusions. The results of the study indicate that IUAE-CEPA provides significant opportunities to accelerate the achievement of Indonesia's economic interests by obtaining a trade surplus through the utilization of non-oil and gas sectors, increasing investment commitments, implementing export market diversification policies to the Middle East region, and the prospects for developing its halal economic sector.